The Role of Satellite Television Channels in The Political socialization (A Field Study in Lattakia) - Zreika, Yousra; Dannoura, Amjad (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
With the momentum in the Presents of the Plethora of events on the political arena، The media plays a great role in shaping the political socialization of a large number of The population who depend on The media as a source of information. Moreover، With the public Concern and political controversy that is taking place nowadays on different levels and in different fields، Most people have Started to express their opinion in accordance with information that they draw on from. what they read or watch through the media. The Current research discusses the role of satellite channels in shaping the political socialization. To achieve the objectives of this study، a questionnaire was designed and administered as Sample of /381/ residents of neighborhoods bsnada and the seventh of April. The results of the study showed that there is a statistically significant difference between the role of the satellite channels in political education and the educational level of the participants. It also revealed that there is a statistically significant difference between the role of the satellite channels in political education and gender.